Characterization of mixed-component oleogels: Beeswax and glycerol monostearate interactions towards Tenebrio Molitor larvae oil - Sohui Jeong; Imkyung Oh (Current Research in Food Science, 2024)
Edible insects are attracting attention as an alternative food due to their excellent production efficiency, lower carbon consumption, and containing high protein. Tenebrio Molitor larvae (TM), one of the approved edible insects worldwide, contain more than 30 % fat content consisting of 70 % unsaturated fatty acids, and particularly high phospholipids. Most of the research has focused on the utilization of proteins, and there are few studies using oils from TM. Therefore, in this study, to expand the utilization of TM oil in food applications, the oleogel was prepared with TM oil fortified by the incorporation of beeswax (BSW) and glycerol monostearate (GMS), and their structure, rheological and thermal properties were evaluated. The interaction between BSW and GMS contributed to the strength of the oleogel structure. The addition of GMS or the increase of the gelator concentrations resulted in increasing the melting point, which is consistent with the observed increase in viscoelasticity. As the temperature increased, the solid fat content decreased. The result of FT-IR suggests that TM oil is physically solidified without changing chemical composition through oleogelation. This study suggests a new processing direction for edible insects by confirming the rheological, thermal, and physicochemical characteristics of TM oil-based oleogel.